Improved resistance-welded joints of thermosetting composites via flame-grown carbon nanotube. Issue 13 (3rd July 2021) - Cui, Xu; Wang, Daosheng; Wang, Shuo; Wei, Jian; Tian, Lin; Deng, Yingfan; Xiong, Xuhai
Abstract: The surface of stainless steel (SS) mesh was modified by in-situ growing carbon nanotubes (CNTs) from ethanol flame. Then the interfacial bond strength of SSM and polyetherimide (PEI) was improved by the CNTs-modified SSM, a heating element (HE) for the resistance welding of carbon fiber reinforced epoxy (CF/Epoxy) laminates. The effects of CNTs growth time ( tg ) on the wettability of PEI solution to SS mesh, interfacial microstructure, and mechanical properties of the welded joint were investigated. The results indicated that the addition of CNTs increased the wettability of PEI solution to SS mesh due to the capillary action of high porosity CNTs coating. The microstructure of the welded joints changed with tg . The maximum single lap shear strength (SLSS) value of the welded joint reached 24.7 MPa when tg  = 10 min. The strengthening mechanism of CNTs and the failure modes of the welded joints were systematically analyzed.